Rethinking Friedrich Meinecke's historicism - Paddock, Troy R. E. (Rethinking History, 2006)
This essay revisits the work of the German historian Friedrich Meinecke and offers new interpretation of his major works, Weltbürgertum und Nationalstaat (1907), Die Ideen der Staatsräson in der neuen Geschichte (1924), and Die Entstehung des Historismus (1936). The standard interpretation of Meinecke's work maintains that World War I caused a break in his thinking and caused him to rethink the role of power in the state. By stressing the first half of Weltbürgertum rather than the second, this article delineates a continuity of Meinecke's thought and points to the limitations of historicism as a historical narrative. It offers a possible explanation for how the conservative implications in the thought of an individual, who personally and politically was a Vernuftrepublikaner, could escape the author himself. This article also discusses what could be called the classical liberal critique of Meinecke's historicism, points to some of its limitations, and offers a more measured criticism of Meinecke that examines him on his own terms—and finds him wanting.
Keywords: Classical liberalism; Historicism; Historiography; Meinecke; Natural law; State; dept.his